2000
DOI: 10.1001/archderm.136.12.1487
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Receptor–Associated Periodic Syndrome

Abstract: Background: Tumor necrosis factor receptorassociated periodic syndrome (TRAPS) is an inflammatory disorder characterized by prolonged episodes of periodic fever and localized inflammation and dominantly inherited mutations in TNFRSF1A, the gene encoding the 55-kDa tumor necrosis factor receptor. To our knowledge, the cutaneous pathologic characteristics of TRAPS have not been described previously.Objectives: To characterize the dermatologic manifestations of TRAPS by clinical, microscopic, and molecular method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…Ocular inflammation with per-orbital edema or conjunctivitis is common. Arthralgia is more prominent than arthritis [82, 85]. …”
Section: Underlying Causes Of Secondary Amyloidosismentioning
confidence: 99%
“…Ocular inflammation with per-orbital edema or conjunctivitis is common. Arthralgia is more prominent than arthritis [82, 85]. …”
Section: Underlying Causes Of Secondary Amyloidosismentioning
confidence: 99%
“…Chest pain can be caused by either aseptic pleural inflammation, or elective involvement of thoracic muscles: the overall duration of symptoms of polyserositis may vary from a few days to several weeks, much longer than that in FMF, usually accompanied by high-grade fever and resolving without any specific treatment [26]. Pleuritic chest pain was described for the first time in 40% of children with a genetically confirmed diagnosis of TRAPS, recruited by the National Institute of Health Clinical Centre in Bethesda [27]. Pelagatti et al reported the clinical features of 11 Italian patients with TRAPS, aiming to analyze the long-term impact of the R92Q TNFRSF1A mutation in these children, who displayed a lower frequency of typical TRAPS manifestations, and they noted that recurrent febrile thoracic pain/pleuritis occurred in 27.2% of cases [28].…”
Section: Tumor Necrosis Factor Receptor-associated Periodic Syndromementioning
confidence: 99%
“…Sometimes, in addition to fever, the attacks are characterized by severe abdominal pain, which may mimic a surgical emergency. Cutaneous manifestations are present in 87% of patients during attacks [33]. Most patients exhibit localized painful erythematous macules and patches that tend to migrate to the distal parts of the extremities.…”
Section: Clinical Considerations and Treatmentmentioning
confidence: 99%